Outcome of Twins Discordant for Major Anomalies - Bhutia, Tseten Zangmu; Kolar, Geeta; Kavuri, Kamala; Redishetty, Saritha; Reddy, Prathiba; Singh, Arati; Pawar, Smita; Kachakayala, Mounika; Shivaramegowda, Raksha; Vavilala, Suseela (Journal of Fetal Medicine, 2024)
Objectives This article determines the incidence, management, and outcomes of twins discordant for major structural anomalies.Materials and Methods A retrospective observational study was conducted from 2011 to 2021. Pregnant women discordant for major malformations as confirmed postnatally were included in the study. Demographic and clinical details were collected from medical records. Determining the incidence and profile of twins discordant for major structural anomalies and their management and outcomes were considered as primary objectives that were detailed in dichorionic (DC) and monochorionic (MC) twin pregnancies.Results A total of 83 subjects were included, with an incidence of 1.76% in DC pregnancies and 1.4% in MC pregnancies. Major structural anomalies among DC twins were musculoskeletal (26%), followed by circulatory system anomalies (20.2%), while among MC twins, the majority were found to be central nervous system anomalies (35.7%). Gastrointestinal system anomalies were found the least, with 5.8% in DC anomalous twins, and none were observed in MC anomalous twins. Live birth rate among anomalous twins was found to be 79.71 and 64.29%, and in normal cotwins, it was 92.75 and 85.71% in DC and MC twins, respectively. Surviving anomalous twins underwent postnatal surgery or intervention in 25/69 (36.2%) DC twins, out of which 20 infants were alive and healthy. In the MC anomalous twin group, 3/14 (21.42%) underwent surgical correction; all were alive and well. Postnatally, babies were followed up until 2 years of life. The survival rate for anomalous twins was 47.82% in DC and 35.7% in MC twins. Normal cotwins had overall favorable outcomes, with a survival rate of 89.8 and 85.7% in DC and MC twins, respectively.Conclusion In DC twins discordant for major anomalies, expectant management is a safe option.
Keywords: discordant twins; dichorionic twins; monochorionic twins; fetal outcomes; postnatal surgery